A nationwide analysis of 30-day readmissions related to critical limb ischemia. (June 2018) - Masoomi, Reza; Shah, Zubair; Quint, Clay; Hance, Kirk; Vamanan, Karthik; Prasad, Anand; Hoel, Andrew; Dawn, Buddhadeb; Gupta, Kamal
Objectives: There is paucity of information regarding critical limb ischemia-related readmission rates in patients admitted with critical limb ischemia. We studied 30-day critical limb ischemia-related readmission rate, its predictors, and clinical outcomes using a nationwide real-world dataset. Methods: We did a secondary analysis of the 2013 Nationwide Readmissions Database. We included all patients with a primary diagnosis of extremity rest pain, ulceration, and gangrene secondary to peripheral arterial disease. From this group, all patients readmitted with similar diagnosis within 30 days were recorded. Results: Of the total 25, 111 index hospitalization for critical limb ischemia, 1270 (5%) were readmitted with a primary diagnosis of critical limb ischemia within 30 days. The readmission rate was highest (9.5%) for the group that did not have any intervention (revascularization or major amputation) and was lowest for surgical revascularization and major amputation groups (2.6% and 1.3%, P value <0.001 for all groups). Severity of critical limb ischemia at index admission was associated with a significantly higher rate of 30-day readmission. Critical limb ischemia-related readmission was associated with a higher rate of major amputation (29.6% vs. 16.2%, P <0.001), a lower rate of any revascularization procedure (46% vs. 62.6%, P <0.001), and a higher likelihood of discharge to a skilled nursing facility (43.2% vs. 32.2%, P <0.001) compared to index hospitalization. Conclusions: In patients with primary diagnosis of critical limb ischemia, 30-day critical limb ischemia-related readmission rate was affected by initial management strategy and the severity of critical limb ischemia. Readmission was associated with a significantly higher rate of amputation, increased length of stay, and a more frequent discharge to an alternate care facility than index admission and thus may serve as a useful quality of care metric in critical limb ischemia patients.